ἀρέσκω, ἀπαρέσκω (with accusative or dative) (Moer. η 6, [Hdn.] Philet. 88) - Cluyse, Brian (My University, 2025)
This article provides a philological and linguistic commentary on the argument structure alternation between the Nominative-Accusative and the Nominative-Dative with the Ancient Greek verbs ἀρέσκω and ἀπαρέσκω. Starting from the first recorded discussion of this alternation in the Atticist lexica Moer. η 6 and [Hdn.] Philet. 88, I assess the linguistic validity of the Atticists’ labels κοινόν/κοινῶς en Ἀττικοί/ἀττικῶς and track the diachronic development of the alternation from Homeric to Modern Greek. I pay particular attention to how animacy, diathesis, (pro)nominality and genre/register relate to a difference in case marking (Accusative or Dative).
PUBLISHED
Keywords: Accusative; Dative; Argument structure alternation; Diachronic change; Syntax; ANCIENT GREEK CULTURE AND CONTEMPORARY CRITICAL THOUGHT; Ancient Greek Culture and Literature; Greek comedy; Greek epic and post-classical poetry; Greek tragedy, Euripides; LINGUISTICS; MORPHOLOGIC FEATURES; MORPHOLOGY; SYNTAX; diachronic syntax